Novel Evidence-Based Labor Induction Algorithm Associated with Increased Vaginal Delivery within 24 Hours - Kuba, Kfier; Estrada-Trejo, Fatima; Lambert, Calvin; Vani, Kavita; Eisenberg, Ruth; Nathan, Lisa; Bernstein, Peter; Hughes, Francine (American Journal of Perinatology, 2022)
Objective This study aimed to assess whether concordance with our proposed labor induction algorithm is associated with an increased rate of vaginal delivery within 24 hours.Study Design We conducted a retrospective review of 287 induction of labors (IOLs) at a single urban, tertiary, academic medical center which took place before we created an evidence-based IOL algorithm. We then compared the IOL course to the algorithm to assess for concordance and outcomes. Patients age 18 years or over with a singleton, cephalic pregnancy of 366/7 to 420/7 weeks' gestation were included. Patients were excluded with a Bishop's score >6, contraindication to misoprostol or cervical Foley catheter, major fetal anomalies, or intrauterine fetal death. Patients with 100% concordance were compared with <100% concordant patients, and patients with ≥80% concordance were compared with <80% concordant patients. Adjusted hazard ratios (AHRs) were calculated for rate of vaginal delivery within 24 hours, our primary outcome. Competing risk's analysis was conducted for concordant versus nonconcordant groups, using vaginal delivery as the outcome of interest, with cesarean delivery (CD) as a competing event.Results Patients with 100% concordance were more likely to have a vaginal delivery within 24 hours, n = 66 of 77 or 85.7% versus n = 120 of 210 or 57.1% (p < 0.0001), with an AHR of 2.72 (1.98, 3.75, p < 0.0001) after adjusting for delivery indication and scheduled status. Patients with 100% concordance also had shorter time from first intervention to delivery (11.9 vs. 19.4 hours). Patients with ≥80% concordance had a lower rate of CD (11/96, 11.5%) compared with those with <80% concordance (43/191 = 22.5%; p = 0.0238). There were no differences in neonatal outcomes assessed.Conclusion Our IOL algorithm may offer an opportunity to standardize care, improve the rate of vaginal delivery within 24 hours, shorten time to delivery, and reduce the CD rate for patients undergoing IOL.Key Points
Keywords: labor; induction; algorithm; induction of labor; misoprostol; Foley catheter; oxytocin; standardize